2021
DOI: 10.3322/caac.21657
|View full text |Cite
|
Sign up to set email alerts
|

Current treatment and recent progress in gastric cancer

Abstract: Gastric cancer is not a top-10 malignancy in the United States but represents one of the most common causes of cancer death worldwide. Biological differences between tumors from Eastern and Western countries add to the complexity of identifying standard-of-care therapy based on international trials. Systemic chemotherapy, radiotherapy, surgery, immunotherapy, and targeted therapy all have proven efficacy in gastric adenocarcinoma; therefore, multidisciplinary treatment is paramount to treatment selection. Trip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
841
2
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,067 publications
(858 citation statements)
references
References 96 publications
(172 reference statements)
8
841
2
7
Order By: Relevance
“…In recent years, tumor immunotherapy has received extensive attention in a variety of solid tumors and has been regarded as an important treatment method (Kirkwood et al, 2012). For example, the application of programmed death 1 (PD-1) inhibitors in ESCA, advanced liver cancer, and locally advanced or metastatic GC has achieved good curative effects (Högner and Thuss-Patience, 2021;Joshi and Badgwell, 2021;Kim et al, 2021). Related studies have shown that some SMYD family members are closely related to immune infiltration (Stender et al, 2012;Nagata et al, 2015;Xu et al, 2015), but the underlying immune mechanism in tumors remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, tumor immunotherapy has received extensive attention in a variety of solid tumors and has been regarded as an important treatment method (Kirkwood et al, 2012). For example, the application of programmed death 1 (PD-1) inhibitors in ESCA, advanced liver cancer, and locally advanced or metastatic GC has achieved good curative effects (Högner and Thuss-Patience, 2021;Joshi and Badgwell, 2021;Kim et al, 2021). Related studies have shown that some SMYD family members are closely related to immune infiltration (Stender et al, 2012;Nagata et al, 2015;Xu et al, 2015), but the underlying immune mechanism in tumors remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…According to the report recently released by the International Agency for Research on Cancer, GC remains one of the most common causes of cancer death worldwide. Although multidisciplinary treatment has made big progress 1 , GC still ranked the fth for incidence and the fourth for mortality globally 2 . The understanding of the pathogenesis and development mechanism of GC is attracting considerable attention in order to nd effective therapeutic and prevention strategies.…”
Section: Introductionmentioning
confidence: 99%
“…More than one-third of all GC patients have distant metastasis (stage IV) at diagnosis. The survival time of these patients is short, rarely more than one year, and the treatment options are limited, including palliative chemotherapy, immunotherapy, and targeted therapy [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%